2011
DOI: 10.1002/14651858.cd008112.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Spinal manipulative therapy for chronic low-back pain

Abstract: Background Many therapies exist for the treatment of low-back pain including spinal manipulative therapy (SMT), which is a worldwide, extensively practiced intervention. Objectives To assess the effects of SMT for chronic low-back pain. Search methods An updated search was conducted by an experienced librarian to June 2009 for randomised controlled trials (RCTs) in CENTRAL (The Cochrane Library 2009, issue 2), MEDLINE, EMBASE, CINAHL, PEDro, and the Index to Chiropractic Literature. Selection criteria RCTs whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(61 citation statements)
references
References 128 publications
2
49
0
6
Order By: Relevance
“…14 Because SM involves the application of physical force, there is a potential risk of traumatic injury, should the manipulation be lacking in technical skill or precision, provided to individuals particularly vulnerable to injury, or otherwise misapplied. However, the risk of injury to the head, neck or trunk following SM remains uncertain, particularly for older adults.…”
Section: Introductionmentioning
confidence: 99%
“…14 Because SM involves the application of physical force, there is a potential risk of traumatic injury, should the manipulation be lacking in technical skill or precision, provided to individuals particularly vulnerable to injury, or otherwise misapplied. However, the risk of injury to the head, neck or trunk following SM remains uncertain, particularly for older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for falls in older adults include increasing age, medication use, unsteady gaits, confusion, cognitive impairment, and sensory deficits. However, research has shown that attention to these risk factors can significantly reduce the rates of falls [4]. Therefore, to develop quality fall prevention strategies, an assessment of balance among the persons concerned is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies on fall prevention currently include middle-aged participants. However, new study data confirm the effectiveness of numerous interventions in preventing falls, including fall-risk assessments related to interventions, exercise, environmental inspection and modification, and combined interventions [4,14]. Physical exercise and balance training have benefited older adults, which may also extend to middle-aged adults.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, acupuncture, yoga, and spinal manipulation showed significant effects for treating back pain [9, 24, 25]. Evidence from systematic reviews shows that spinal manipulation has small effects short term, but unclear effects long term [26, 27]. Pharmacotherapies are only evaluated for short-term use up to 3 months and have medium (opiates) to small effects (nonsteroidal anti-inflammatory drugs [NSAIDs], SSRIs, tricyclic antidepressants) vis-à-vis placebo, and long-term use is neither well researched nor recommended [28].…”
Section: Introductionmentioning
confidence: 99%